Portable Real-Time Monitoring System for PT PLN ULP Cikarang Distribution Substation Based on IoT and PZM 004T Sensor - Simatupang, Joni Welman; Aziz, Moch (Teknik Elektro Universitas Siliwangi, 2024)
One of PT PLN ULP Cikarang Kota's commitments is to maintain the quality level of electricity services to maintain reliability and ensure the sustainability of electrical energy distribution. Maintenance of distribution transformers is an important key in making this happen. The effectiveness of using distribution transformers is 80% of the total capacity to prevent interference. Currently there is no tool available that can detect overload and record peak load times. This research realizes real-time monitoring of distribution substations in the PT PLN ULP Cikarang Kota area using the PZEM 004T sensor and IoT-based. The PZEM 004T sensor sends the reading results to the ESP32 microcontroller to be processed and sent to the ThingSpeak page. The reading results become material for analyzing usage patterns and the basis for making decisions on measures to prevent distribution transformer disturbances. The research was conducted at three distribution substations with residential, industrial, and a combination of residential and industrial customer types. The research results showed that the voltage at the home customer substation was normal and the purely industrial customer substation as well as the industrial and home customer substation experienced over voltage of 0.6% and 1.5%. The loading of distribution substations for industrial and home customers experienced an overload of 147% and the loading of all types of substations experienced unbalance with the highest imbalance of 77% at purely industrial customer substations.